Composite hydrogel, preparation method and friction nano generator
By modifying MXene with tannin and oxidized cellulose nanofibers, modifying MXene and combining it with gel material to prepare a composite hydrogel, which solves the problems of MXene easy to oxidize and self-stack, improves the conductivity and mechanical properties of the hydrogel, and is suitable for the construction of flexible friction nanogenerators.
Patent Information
- Application Number
- CN202510077789.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-11
AI Technical Summary
The application of existing hydrogels in friction nanogenerators is limited by problems such as poor mechanical properties, low conductivity and slow response to external stimuli. MXene nanosheets are prone to oxidation and self-stacking, which affects performance.
A composite hydrogel was prepared by using tannin and oxidized cellulose nanofibers to modify MXene to form modified MXene and combined with gel material. The composite hydrogel improves its dispersion uniformity and oxidation resistance in aqueous solution by improving the hydrophilicity and mechanical properties of MXene.
The stability and dispersion of modified MXene in solution have been significantly improved, and the composite hydrogel shows excellent conductivity and mechanical properties, which are suitable for building flexible friction nanogenerators.
Smart Images

Figure CN119798533A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of biomedical engineering materials, and in particular to a composite hydrogel, a preparation method and a friction nanogenerator. Background Art
[0002] Compared with traditional metal electrodes, hydrogels have become emerging candidates for constructing stretchable electrodes for triboelectric nanogenerators (TENGs) due to their softness similar to biological tissues, good stretchability, stimulus responsiveness, and biocompatibility. However, disadvantages such as poor mechanical properties, relatively low electrical conductivity, and slow response to external stimuli have greatly limited the practical application of hydrogels in TENGs. A simple but effective strategy to improve the conductivity of hydrogels is to incorporate conductive nanofillers into the hydrogel network. However, conductive nanofillers such as graphene, carbon nanotubes, and metal nanowires are easily aggregated in polymer matrices due to their poor hydrophilicity and lack of functional groups, thereby reducing the conductivity and mechanical properties of hydrogels.
[0003] In recent years, MXene nanosheets have been widely used as nanofillers to prepare conductive hydrogels due to their excellent metallic conductivity, hydrophilicity, and mechanical properties. Although the abundant hydrophilic groups on the surface of MXene promote interfacial compatibility with hydrogel polymers, MXene nanosheets are easily oxidized in the presence of dissolved oxygen and water molecules. In addition, the interlayer interaction of MXene nanosheets promotes self-stacking and leads to aggregation, which reduces the performance of hydrogels and further affects the output performance of TENG. Therefore, designing a stable MXene-based composite hydrogel with excellent mechanical properties is an urgent need for constructing flexible TENG. Summary of the invention
[0004] In view of the above problems in the prior art, the present application provides a composite hydrogel, a preparation method and a friction nanogenerator. The specific technical solution is as follows:
[0005] On the one hand, the present application provides a composite hydrogel, which includes a gel material and a modified MXene, wherein the modified MXene is obtained by surface-modifying MXene with tannic acid and oxidized cellulose nanofibers.
[0006] In a possible embodiment, the modified MXene satisfies at least one of the following characteristics:
[0007] The mass ratio of the oxidized cellulose nanofibers, the tannic acid and the MXene in the modified MXene is 0.1-1.5:1:1;
[0008] The chemical formula of the MXene is Ti3C2Tx, wherein Tx includes at least one of -O, -OH and -F.
[0009] In a possible implementation manner, the mass ratio of the gel material and the modified MXene in the composite hydrogel is 65:1-2.
[0010] In a possible implementation, the gel material includes at least one of polyacrylamide, polyhydroxyethyl methacrylate, polyacrylic acid and polyethylene glycol.
[0011] On the other hand, the present application also provides a method for preparing a composite hydrogel, comprising:
[0012] S1: Provide MXene, tannic acid, oxidized cellulose nanofibers and gel monomers;
[0013] S2: mixing the MXene and the tannic acid in a solvent to obtain a mixed solution;
[0014] S3: adding the oxidized cellulose nanofibers into the mixed solution to obtain a modified MXene dispersion;
[0015] S4: Mixing and cross-linking the modified MXene dispersion with the gel monomer to obtain a composite hydrogel.
[0016] In a possible implementation manner, the S1 includes:
[0017] Providing lithium fluoride powder, titanium aluminum carbide powder and hydrochloric acid;
[0018] dissolving the lithium fluoride powder in the hydrochloric acid to obtain a hydrofluoric acid solution;
[0019] Adding the titanium aluminum carbide powder into the hydrofluoric acid solution to react and obtain a MXene mixed solution;
[0020] The MXene mixed liquid is washed and collected to obtain the MXene.
[0021] In a possible implementation manner, S2 satisfies at least one of the following characteristics:
[0022] The pH of the solvent is 8-9;
[0023] The mixing time is 11-13 hours.
[0024] In a possible implementation manner, the S4 includes:
[0025] Provide initiators, cross-linkers and catalysts;
[0026] The modified MXene dispersion, the gel monomer, the initiator, the cross-linking agent and the catalyst are fully mixed and reacted to obtain the composite hydrogel.
[0027] In a possible implementation, the initiator includes at least one of ammonium persulfate and sodium persulfate.
[0028] In a possible implementation, the cross-linking agent includes at least one of N,N-methylenebisacrylamide and ethylene glycol dimethacrylate.
[0029] In a possible implementation, the catalyst includes at least one of triethylenediamine and tetramethylethylenediamine.
[0030] On the other hand, the present application also provides a friction nanogenerator, comprising the composite hydrogel as described above.
[0031] Based on the above technical solution, this application has the following beneficial effects:
[0032] In the present application, MXene is surface-modified by tannic acid and oxidized cellulose nanofibers to obtain modified MXene. Tannic acid can react with water and oxygen to consume oxidation sources, and can also form coordination bonds with metal atoms on the surface of MXene, which is beneficial to protect MXene from oxidation. In addition, both tannic acid and oxidized cellulose nanofibers have abundant hydrophilic groups, which can improve the hydrophilicity of MXene, thereby improving the dispersion uniformity of MXene in aqueous solution, and effectively improving the problem of easy oxidation and self-stacking of MXene nanosheets. In addition, the functional groups in tannic acid and oxidized cellulose nanofibers can form a large number of hydrogen bonds with the gel material, so that the composite hydrogel exhibits excellent tensile properties, which is beneficial to further construct a flexible friction nanogenerator containing the composite hydrogel. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions and advantages in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0034] Figure 1 : Comparison of the stability of a modified MXene dispersion and a MXene dispersion provided in the examples of the present application;
[0035] Figure 2 : A picture of a composite hydrogel in a natural state provided in an embodiment of the present application;
[0036] Figure 3: A picture of a composite hydrogel in a stretched state provided in an embodiment of the present application;
[0037] Figure 4 : A flow chart of the preparation of a composite hydrogel provided in an embodiment of the present application;
[0038] Figure 5 : A schematic diagram of the structure of a friction nanogenerator provided in an embodiment of the present application;
[0039] Figure 6 : Pictures of a friction nanogenerator provided in an embodiment of the present application in different states;
[0040] Figure 7 : A schematic diagram of a working mode of a friction nanogenerator provided in an embodiment of the present application;
[0041] Figure 8 : Voltage-time diagram of a friction nanogenerator provided in an embodiment of the present application when worn on different parts of the human body;
[0042] Fig. 9 : A voltage-time diagram of a friction nanogenerator provided in an embodiment of the present application under different motion states of the human body;
[0043] Fig.10 : Comparison of stress-strain curves of Example 1 and Comparative Examples 1-3;
[0044] Fig.11 : Comparison of fracture energy of Example 1 and Comparative Examples 1-3;
[0045] Fig.12 : Stress-strain curve of Example 1 after repeated stretching for 5 cycles;
[0046] Fig.13 : Comparison of temperature variation-time curves of Example 2 and Comparative Example 4 under illumination conditions;
[0047] Fig.14 : Comparison of bacterial survival rates of Example 2 and Comparative Example 4 under different lighting conditions;
[0048] Figure numerals: 1 - first elastic layer, 2 - composite hydrogel layer, 3 - second elastic layer, 4 - external object. DETAILED DESCRIPTION
[0049] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0050] It should be noted that in the description of the present application, for the following defined terms, unless a different definition is given in the claims or elsewhere in this specification, these definitions should be applied. All numerical values, whether or not explicitly indicated, are defined herein as being modified by the term "about". The term "about" generally refers to a numerical range that a person of ordinary skill in the art would consider to be equivalent to the stated value to produce substantially the same properties, functions, results, etc. A numerical range indicated by a low value and a high value is defined to include all numerical values included in the numerical range and all subranges included in the numerical range.
[0051] It should be noted that, in the description of the present application, the terms "first", "second", etc. are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.
[0052] It should be noted that, in the description of the present application, the meaning of the terms "on", "above", "above", and "above" should be interpreted in the broadest sense, meaning that the description containing these terms is interpreted as "the component can be set on another component in direct contact, or there can be an intermediate component or layer between the components". In addition, for the convenience of description, the present application may also use spatial relative terms such as "under", "below", "under", "on", "above", "above", "lower", "upper", etc. to describe the relationship between an element or component and another element or component shown in the drawings. In addition to the orientations described in the figures, the spatially relative terms are also intended to cover different orientations of the device in use or operation. The device can be oriented in other ways (rotated 90° or in other orientations), and the spatially relative descriptors used in the present application can be interpreted accordingly.
[0053] The present application provides a composite hydrogel, which includes a gel material and a modified MXene. The modified MXene is obtained by surface modification of MXene with tannic acid and oxidized cellulose nanofibers. Tannic acid can preferentially react with water and oxygen to consume oxidation sources, and can also form coordination bonds with metal atoms on the surface of MXene, which is beneficial to protect MXene from oxidation; and both tannic acid and oxidized cellulose nanofibers have abundant hydrophilic groups, which can improve the hydrophilicity of MXene, thereby improving the dispersibility of MXene in aqueous solution, and effectively improving the problem of easy oxidation and self-stacking of MXene nanosheets. In addition, the functional groups in tannic acid and oxidized cellulose nanofibers can form a large number of hydrogen bonds with the gel material, so that the composite hydrogel exhibits excellent mechanical properties, which is beneficial to further construct a friction nanogenerator containing the composite hydrogel.
[0054] In some embodiments, the mass ratio of oxidized cellulose nanofibers, tannic acid and MXene in the modified MXene is 0.1-1.5:1:1; it can be understood that the mass ratio of oxidized cellulose nanofibers, tannic acid and MXene in the modified MXene can be any point value in 0.1-1.5:1:1; illustratively, the mass ratio of oxidized cellulose nanofibers, tannic acid and MXene in the modified MXene can be 0.1:1:1, 0.2:1:1, 0.5:1:1, 0.8:1:1, 1:1:1, 1.5:1:1, etc. In this way, the mass ratio of oxidized cellulose nanofibers, tannic acid and MXene is controlled within the above range, which can effectively avoid the oxidation of MXene in the presence of dissolved oxygen and water molecules, and avoid the self-stacking promoted by the interaction between MXene layers, so that the modified MXene can maintain stability and uniform dispersion in the solvent. Preferably, the mass ratio of oxidized cellulose nanofibers, tannic acid and MXene in the modified MXene is 1:1:1.
[0055] In order to demonstrate the stability of modified MXene in oxygen-containing solution, Figure 1 The stability of MXene and modified MXene after adding 0.3wt% hydrogen peroxide solution is shown, and the state of MXene and modified MXene at 3 days and 11 days is compared. Figure 1 It can be seen that MXene showed obvious stratification on the third day after the addition of 0.3wt% hydrogen peroxide solution, and obvious precipitation and supernatant appeared on the 11th day, proving that MXene has been oxidized and stacked in the oxygen-containing solution; while the modified MXene was evenly dispersed on the third and 11th days after the addition of 0.3wt% hydrogen peroxide solution, without obvious stratification, proving that the modified MXene has good antioxidant properties and stability compared with before modification.
[0056] Specifically, the chemical formula of MXene is Ti3C2Tx, where Tx includes at least one of -O, -OH and -F, has excellent conductivity and large specific surface area, which helps to improve its energy density and efficiency in the energy storage process; Ti3C2Tx has good flexibility and mechanical properties and is suitable for the preparation of flexible electronic devices.
[0057] Specifically, the oxidized cellulose nanofiber is TEMPO (2,2,6,6-tetramethylpiperidinyl oxide) oxidized cellulose nanofiber. TEMPO oxidized cellulose nanofiber is a nanoscale cellulose material obtained by subjecting natural cellulose to TEMPO oxidation treatment. It has good biodegradability and environmental friendliness and is suitable for environmentally friendly materials and biomedical fields.
[0058] In some embodiments, the mass ratio of the gel material and the modified MXene in the composite hydrogel is 65:1-2; it can be understood that the mass ratio of the gel material and the modified MXene in the composite hydrogel is any point value in 65:1-2; illustratively, the mass ratio of the gel material and the modified MXene in the composite hydrogel is 65:1, 65:1.2, 65:1.5, 65:1.7, 65:2, etc. In this way, controlling the mass ratio of the gel material and the modified MXene within the above range is conducive to improving the conductivity of the composite hydrogel, so that the modified MXene can form a conductive network in the composite hydrogel, and effectively improves the mechanical properties of the gel material, which is conducive to improving the mechanical strength and tensile properties of the composite hydrogel.
[0059] Figure 2 The morphology of a composite hydrogel provided in the embodiment of the present application in a natural state is shown. Figure 3 The morphology of a composite hydrogel in a stretched state provided in the embodiment of the present application is shown. Figure 2 and Figure 3 It can be seen that the length of the composite hydrogel in the stretched state can reach about 8 times the length before stretching, and the composite hydrogel after stretching does not show damage or breakage, which proves that the composite hydrogel has good mechanical properties.
[0060] Specifically, the gel material includes at least one of polyacrylamide, polyhydroxyethyl methacrylate, polyacrylic acid and polyethylene glycol, has good hydrophilicity, can be fully mixed with modified MXene to obtain a composite hydrogel with conductive properties; and has good biocompatibility, can be applied in the biomedical field, and is suitable for the preparation of flexible wearable products.
[0061] The following combination Figure 4A method for preparing a composite hydrogel provided in an embodiment of the present application is introduced. This specification provides method operation steps as in the embodiment, but more or fewer operation steps may be included based on conventional or non-creative labor. The order of steps listed in the embodiment is only one way of executing the order of many steps and does not represent the only execution order. When the preparation method is actually executed, it can be executed in the order of the method shown in the embodiment or the accompanying drawings or in parallel. A method for preparing a composite hydrogel provided in the present application may include S1-S4:
[0062] S1: Provide MXene, tannic acid, oxidized cellulose nanofibers and gel monomers;
[0063] In some embodiments, step S1 includes: providing lithium fluoride powder, titanium aluminum carbide powder and hydrochloric acid; dissolving lithium fluoride powder in hydrochloric acid to obtain a hydrofluoric acid solution; slowly adding titanium aluminum carbide powder to the hydrofluoric acid solution for etching to obtain a MXene mixture; washing and collecting the MXene mixture to obtain MXene. The chemical formula of the prepared MXene is Ti3C2Tx. Through the above method, a single-layer MXene with a stable structure can be prepared, which is beneficial to improve the specific surface area and conductivity of MXene, and is suitable for applications such as energy storage and conversion.
[0064] Specifically, the concentration of hydrochloric acid is 9M, and the ratio of the amount of lithium fluoride powder to the amount of hydrochloric acid is 2g:30-50mL; it is understandable that the amount of lithium fluoride powder to the amount of hydrochloric acid can be any point value in 2g:30-50mL, which is not enumerated here. Specifically, the mass ratio of lithium fluoride powder to titanium aluminum carbide powder is 1:0.5-1; it is understandable that the mass ratio of lithium fluoride powder to titanium aluminum carbide powder can be any point value in 1:0.5-1, which is not enumerated here.
[0065] In some embodiments, the cleaning process includes: adding deionized water to the MXene mixed solution, centrifuging until the pH value of the supernatant after centrifugation is greater than or equal to a preset pH, thereby obtaining a first supernatant and a first precipitate; removing the first supernatant, adding anhydrous ethanol to the first precipitate, and ultrasonically treating the first precipitate to obtain a MXene pretreatment solution; centrifuging the MXene pretreatment solution to obtain a second precipitate; adding deionized water to the second precipitate, ultrasonically dispersing and centrifuging, and collecting the black-brown supernatant as a MXene monolayer dispersion.
[0066] Specifically, the preset pH is 6-7. It can be understood that the preset pH can be any point value between 6 and 7, which is not enumerated here. Repeating the centrifugation process until the supernatant after centrifugation is greater than or equal to the preset pH can ensure that the acidic impurities in the MXene mixture are effectively removed, which is conducive to the preparation of pure MXene.
[0067] Specifically, the ultrasonic time is 1-2 hours; it can be understood that the ultrasonic time can be any point value between 1-2 hours; illustratively, the ultrasonic time can be 1 hour, 1.2 hours, 1.5 hours, 1.7 hours, 2 hours, etc., which can expand the interlamellar spacing and specific surface area of MXene, and is conducive to obtaining stable single-layer MXene nanosheets.
[0068] In some embodiments, the collection process includes: freezing and drying the MXene monolayer dispersion to obtain MXene.
[0069] S2: mixing MXene and tannic acid in a solvent to obtain a mixed solution;
[0070] Specifically, the pH of the solvent during the mixing process is 8-9; it is understandable that the pH of the solvent can be any value between 8 and 9, which is not enumerated here. In this way, the pH of the solvent is controlled within the above range, which is conducive to reducing the oxidation reaction in the mixed solution and ensuring the stability of MXene in the mixed solution.
[0071] Preferably, the solvent is deionized water, so that MXene, tannic acid, oxidized cellulose nanofibers and gel monomers can be evenly dispersed in the solvent. Deionized water is used as the solvent, which is safer and avoids the safety hazards caused by organic solvents.
[0072] Specifically, stirring is performed during the mixing process, and the stirring time is 11-13 hours; it can be understood that the stirring time is any point value between 11-13 hours; illustratively, the stirring time is 11 hours, 11.5 hours, 12 hours, 12.5 hours, 13 hours, etc. In this way, controlling the stirring time within the above range is conducive to uniform dispersion and full mixing of tannic acid and MXene in the solvent, so that tannic acid can modify the surface of MXene and avoid self-oxidation of MXene in the solution.
[0073] S3: adding oxidized cellulose nanofibers to the mixed solution and mixing to obtain a modified MXene dispersion;
[0074] Specifically, the mixing time of the oxidized cellulose nanofibers in the mixed solution is 10-20 minutes; it can be understood that the mixing time of the oxidized cellulose nanofibers in the mixed solution can be any point value in 10-20 minutes; illustratively, the mixing time of the oxidized cellulose nanofibers in the mixed solution can be 10 minutes, 12 minutes, 15 minutes, 17 minutes, 20 minutes, etc. In this way, the oxidized cellulose nanofibers can be evenly dispersed in the mixed solution, and the oxidized cellulose nanofibers can modify the surface of the MXene, which is conducive to the preparation of a modified MXene with stability.
[0075] S4: Mixing and cross-linking the modified MXene dispersion with the gel monomer to obtain a composite hydrogel.
[0076] In some embodiments, step S4 includes: providing an initiator, a crosslinker and a catalyst; fully mixing the modified MXene dispersion, the gel monomer, the initiator, the crosslinker and the catalyst, and reacting to obtain a composite hydrogel. The prepared composite hydrogel has good conductivity and can be used to construct a friction nanogenerator; and the rich functional groups in the tannic acid and oxidized cellulose nanofibers can form a large number of hydrogen bonds with the gel material, so that the composite hydrogel exhibits excellent mechanical properties.
[0077] Specifically, the modified MXene dispersion, gel monomer, initiator, cross-linker and catalyst are fully mixed for a preset time, which is the time from the modified MXene dispersion, gel monomer, initiator, cross-linker and catalyst being mixed until they are uniformly mixed. It can be understood that the preset time can be adaptively adjusted according to the specific dispersion conditions.
[0078] Specifically, the initiator includes at least one of ammonium persulfate and sodium persulfate. The initiator can generate free radicals, thereby initiating a polymerization reaction between gel monomers. It can be understood that the corresponding initiator is selected according to different gel monomer materials during the preparation process.
[0079] Specifically, the crosslinking agent includes at least one of N,N-methylenebisacrylamide and ethylene glycol dimethacrylate. The crosslinking agent connects the gel monomers through chemical reaction or physical action to form a stable three-dimensional network structure, thereby enhancing the mechanical strength and stability of the composite hydrogel, and being able to adjust its swelling properties, permeability and biocompatibility. It can be understood that the corresponding crosslinking agent is selected according to different gel monomer materials during the preparation process.
[0080] Specifically, the catalyst includes at least one of triethylenediamine and tetramethylethylenediamine. The catalyst can promote the polymerization reaction between gel monomers, reduce the activation energy of the reaction, and accelerate the reaction rate, thereby making the preparation process of the composite hydrogel more efficient and controllable. It can be understood that the corresponding catalyst is selected according to different gel monomer materials during the preparation process.
[0081] The above preparation method can be used to obtain modified MXene with antioxidant properties and dispersion stability. By mixing and cross-linking the modified MXene with a gel material, a composite hydrogel with good conductive properties can be obtained. The modified MXene can form a large number of hydrogen bonds with the gel material, which is beneficial to improving the mechanical properties of the composite hydrogel. The above preparation method can obtain a composite hydrogel of the size required for practical application by changing the mold size. The operation is convenient, the preparation process is simple, and it is beneficial to reduce the preparation cost.
[0082] On the other hand, the present application also provides a triboelectric nanogenerator, comprising the composite hydrogel as described above. Thus, the composite hydrogel is used as a flexible stretchable electrode to construct a flexible triboelectric nanogenerator, which can improve the problem of poor flexibility and poor skin adhesion of traditional electrode materials.
[0083] In some embodiments, reference Figure 5 The friction nanogenerator comprises a first elastic layer 1, a composite hydrogel layer 2 and a second elastic layer 3. The composite hydrogel layer 2 is disposed between the first elastic layer 1 and the second elastic layer 3. The composite hydrogel layer 2 can be encapsulated by the first elastic layer 1 and the second elastic layer 3 to obtain a friction nanogenerator having a sandwich structure. Preferably, the material of the first elastic layer 1 and the second elastic layer 3 comprises a silicone rubber elastomer, which does not produce harmful substances during the manufacturing process, and is conducive to improving the biocompatibility of the friction nanogenerator; and the silicone rubber elastomer has good elasticity, and can effectively separate and accumulate charges when combined with the composite hydrogel, thereby improving the energy conversion efficiency of the friction nanogenerator.
[0084] Figure 6 The morphology of a friction nanogenerator provided in the embodiment of the present application in a natural state and in a stretched, twisted, and bent state is shown. Figure 6 It can be seen that the friction nanogenerator can be stretched, twisted and bent, and the structure of the friction nanogenerator is not affected under the above conditions, which proves that the friction nanogenerator has good flexibility and structural stability and is suitable for the wearable field.
[0085] Specifically, the thickness of the composite hydrogel layer 2 is 2-4 mm; it can be understood that the thickness of the composite hydrogel layer 2 is any point value between 2-4 mm; illustratively, the thickness of the composite hydrogel layer 2 can be 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, etc. In this way, the thickness of the composite hydrogel layer 2 is controlled within the above range, so that the composite hydrogel layer 2 has good mechanical strength and durability, and is conducive to the generation and collection of charges, thereby improving the power generation efficiency of the friction nanogenerator.
[0086] Specifically, the thickness of the friction nanogenerator is 5-9 mm; it can be understood that the thickness of the friction nanogenerator is any point value between 5-9 mm; illustratively, the thickness of the friction nanogenerator can be 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, etc. The friction nanogenerator provided in the embodiment of the present application has a relatively small thickness, is suitable for wearable devices, and can be implanted in micro devices of relatively small size. It can be understood that the thickness of the friction nanogenerator can be adjusted according to actual needs.
[0087] In some embodiments, the friction nanogenerator also includes a conductive metal sheet and a wire, the conductive metal sheet is at least partially in contact with the composite hydrogel layer 2, and the conductive metal sheet is connected to the wire. The friction nanogenerator can be connected to an external device through the conductive metal sheet and the wire to achieve the output and application of electrical energy.
[0088] Figure 7 The working mode of a friction nanogenerator provided by the embodiment of the present application is shown: ① The friction nanogenerator is grounded, and a resistor R is set on the grounding circuit. When the friction nanogenerator contacts an external object 4, an equal amount of electrostatic charges with opposite signs are generated on the contact surface; ② The external force separates the surface of the friction nanogenerator from the external object 4, forming a small air gap and generating an induced potential difference between the two surfaces; ③ Electrons are exchanged between the friction nanogenerator and the earth to balance the potential change; ④ When the air gap is closed, the potential difference formed by the friction charges disappears, and the electrons flow back. Based on the above working mode, the friction nanogenerator can convert mechanical energy into electrical energy and output electrical energy without connecting to a power supply device.
[0089] In some embodiments, the friction nanogenerator provided by the present application can provide real-time feedback on finger pressing and the movement of various joints of the human body through signals such as voltage, without the need for external power supply equipment. When the friction nanogenerator provided by the present application is applied to the wearable field, it can convert the mechanical energy generated by human movement into electrical energy, reducing the dependence on traditional power sources. Figure 8 and Fig. 9 . Figure 8 The working conditions of a friction nanogenerator provided by the embodiment of the present application when worn on different parts of the human body are demonstrated. Figure 8 The upper left picture shows the working condition of the friction nanogenerator when it is worn on the finger. When the finger is bent, the friction nanogenerator can generate a voltage change of 0-4V, proving that the friction nanogenerator can sense the tiny movement of the human body and generate electric charge; Figure 8 The upper right picture in the middle shows the working condition of the friction nanogenerator when it is worn on the knee. The bending of the knee can produce a voltage change of about 0-15V, proving that larger movements can make the friction nanogenerator generate higher voltage; Figure 8 The lower left picture shows the working condition of the friction nanogenerator when it is worn on the arm. When the arm is bent at an angle greater than 90°, the maximum output voltage of the friction nanogenerator is about 13V, and when the arm is bent at an angle less than 90°, the maximum output voltage is about 5V, proving that the friction nanogenerator can sense the amplitude changes of human body movements. Figure 8The lower right picture shows the working condition of the friction nanogenerator when worn on the wrist. When the wrist is bent downward, the friction nanogenerator can generate a forward voltage of 0-12V, and when the wrist is bent upward, it can generate a reverse voltage of 0-10V, proving that the friction nanogenerator can sense changes in the direction of human body movement.
[0090] Fig. 9 The working conditions of a friction nanogenerator provided by the embodiment of the present application under different motion states of the human body are demonstrated. Fig. 9 The upper left picture shows that the friction nanogenerator can output different voltage curves when writing different letters. The friction nanogenerator can sense the changes in the human body's tiny movements and generate corresponding electrical signals, proving that the friction nanogenerator has high sensitivity; Fig. 9 The lower left figure shows the change in output voltage when the friction nanogenerator is repeatedly pressed with one finger, two fingers, three fingers, and the palm. As the pressure increases, the maximum output voltage of the friction nanogenerator also increases accordingly. Fig. 9 The upper right picture shows a friction nanogenerator placed on the sole of a shoe. When walking, the maximum output voltage of the friction nanogenerator is about 130V, proving that the friction nanogenerator can sense changes in pressure and output a higher voltage under greater pressure. Fig. 9 The lower right picture shows that the friction nanogenerator generates corresponding voltage changes according to the arm swing frequency, and can also output stable voltage when the arm swing frequency is large, proving that the friction nanogenerator can respond quickly when applied and has high output stability.
[0091] Depend on Figure 8 and Fig. 9 It can be seen that the friction nanogenerator provided in the present application has good conductivity and stretchability, can sense tiny changes in movement and adapt to large-scale stretching; and can respond quickly to changes in movement, has high sensitivity, and can realize the detection of human body movement conditions.
[0092] The following combination Figure 10-14 Specific embodiments of the present application are introduced. The following embodiments describe the technical scheme of the present application in more detail, and these embodiments are only for illustrative purposes, because various modifications and changes within the scope of the disclosure of the present application are obvious to those skilled in the art. The reagents used in the embodiments can be obtained by commercial purchase or synthesized according to conventional methods, and can be used directly without further treatment, and the instruments and devices used in the embodiments can be obtained by commercial purchase.
[0093] Example 1
[0094] This embodiment provides a composite hydrogel and a preparation method thereof, wherein the preparation method specifically comprises the following steps:
[0095] 1. Provide MXene, tannic acid, TEMPO oxidized cellulose nanofibers, acrylamide, initiator, crosslinker and catalyst;
[0096] 2. Mix MXene and tannic acid in a mass ratio of 1:1 in deionized water, adjust the pH of the deionized water to 8, and stir for 12 h to obtain a mixed solution;
[0097] 3. Add TEMPO oxidized cellulose nanofibers to the above mixed solution, the mass ratio of TEMPO oxidized cellulose nanofibers to MXene is 1:1, stir for 15 minutes to obtain a modified MXene dispersion;
[0098] 4. Mix the modified MXene dispersion, acrylamide, initiator, cross-linker and catalyst in an ice bath environment, where the mass ratio of modified MXene to gel monomer is 1-2:65, pour into a mold, and cross-link at room temperature to obtain a composite hydrogel.
[0099] Example 2
[0100] The present embodiment provides a friction nanogenerator, comprising a composite hydrogel, a first elastic layer 1 and a second elastic layer 3 as prepared in Example 1, wherein the composite hydrogel is disposed between the first elastic layer 1 and the second elastic layer 3 to form a composite hydrogel layer 2, wherein the thickness of the composite hydrogel layer 2 is 3 mm, and the thickness of the friction nanogenerator is 5 mm.
[0101] Comparative Example 1
[0102] This comparative example provides a composite hydrogel and a preparation method thereof. The similarities between this comparative example and Example 1 are not repeated here. The difference between this comparative example and Example 1 is that the modified MXene dispersion only includes tannic acid and MXene in a mass ratio of 1:1, and does not contain TEMPO oxidized cellulose nanofibers.
[0103] Comparative Example 2
[0104] This comparative example provides a composite hydrogel and a preparation method thereof, the preparation method comprising:
[0105] Acrylamide, TEMPO oxidized cellulose nanofibers, an initiator, a crosslinking agent and a catalyst are provided, and the TEMPO oxidized cellulose nanofibers, acrylamide, the initiator, the crosslinking agent and the catalyst are mixed in an ice bath environment, poured into a mold, and crosslinked at room temperature to obtain a composite hydrogel.
[0106] Comparative Example 3
[0107] This comparative example provides a hydrogel and a preparation method thereof, the preparation method comprising:
[0108] Acrylamide, an initiator, a crosslinking agent and a catalyst are provided, the acrylamide, the initiator, the crosslinking agent and the catalyst are mixed in an ice bath environment, poured into a mold, and crosslinked at room temperature to obtain a polyacrylamide hydrogel.
[0109] Comparative Example 4
[0110] This comparative example provides a friction nanogenerator, including the composite hydrogel prepared in comparative example 3, a first elastic layer 1 and a second elastic layer 3, and the hydrogel is arranged between the first elastic layer 1 and the second elastic layer 3 to form a hydrogel layer, wherein the thickness of the hydrogel layer is 3 mm, and the thickness of the friction nanogenerator is 5 mm.
[0111] Combined with Example 1 and Comparative Examples 1-3, reference Fig.10 , Fig.10 The stress-strain curves of the composite hydrogels in Example 1 and Comparative Examples 1-3 are compared. It can be seen from the figure that the composite hydrogel in Example 1 can withstand a tensile stress of about 50KPa, and the tensile strain is higher than 800%. The tensile stress and tensile strain are both higher than those in Comparative Examples 1-3, which proves that the composite hydrogel in Example 1 has good elastic deformability. Analysis of the stress-strain curves of Comparative Examples 1-3 shows that compared with the polyacrylamide hydrogel in Comparative Example 3, the composite hydrogel containing tannic acid-modified MXene in Comparative Example 1 can withstand a tensile stress greater than 40KPa, and a tensile strain of about 600%, and the composite hydrogel containing TEMPO-oxidized cellulose nanofibers in Comparative Example 2 can withstand a tensile stress of about 30KPa, and a tensile strain greater than 400%. The elastic deformability of Comparative Examples 1 and 2 is better than that of Comparative Example 3, which proves that tannic acid-modified MXene and TEMPO-oxidized cellulose nanofibers are both beneficial to improving the elastic properties of the composite hydrogel.
[0112] Fig.11 The fracture energy of the composite hydrogels in Example 1 and Comparative Examples 1-3 is compared, reflecting the energy consumed by the materials during the fracture process. As can be seen from the figure, the composite hydrogel in Example 1 has a fracture energy higher than 1500 J / m 2 The fracture energy of the composite hydrogels in Comparative Examples 1 and 2 is higher than 1000 J / m 2 And less than 1250J / m 2 The fracture energy of the polyacrylamide hydrogel in Comparative Example 3 is less than 500 J / m 2 , proving that tannic acid-modified MXene and TEMPO-oxidized cellulose nanofibers are beneficial to improving the mechanical properties of the composite hydrogels.
[0113] Fig.12The stress-strain curve of the composite hydrogel in Example 1 after repeated stretching for 5 cycles at a tensile strain of 500% is shown. As can be seen from the figure, during multiple repeated stretching processes, under the same tensile strain, the tensile stress of the composite hydrogel in Example 1 decreases slightly and then tends to stabilize, proving that the composite hydrogel in Example 1 has good durability.
[0114] Combined with Example 2 and Comparative Example 4, reference Fig.13 , Fig.13 The thermal performance of the friction nanogenerators in Example 2 and Comparative Example 4 under illumination conditions is demonstrated. Under the same illumination conditions, the surface temperature of the friction nanogenerator in Example 2 can be increased by 30°C within 300s, while the temperature change of the friction nanogenerator in Comparative Example 4 is only 5°C within 300s. The photothermal conversion efficiency of the friction nanogenerator in Example 2 is significantly better than that of Comparative Example 4, proving that the addition of modified MXene can effectively improve the photothermal performance of polyacrylamide hydrogel, thereby improving the photothermal conversion efficiency of the friction nanogenerator.
[0115] Fig.14 The photothermal antibacterial performance of Example 2 and Comparative Example 4 under no light and light conditions is demonstrated. Under the condition of no near-infrared light irradiation, the bacterial survival rate of the friction nanogenerator in Example 2 and Comparative Example 4 is similar; under the condition of near-infrared light irradiation, the bacterial survival rate of the friction nanogenerator in Example 2 is significantly reduced, and the bacterial survival rate can be reduced from 100% to about 0.01%, while the bacterial survival rate of the friction nanogenerator in Comparative Example 4 is slightly increased compared with the condition of no light, which proves that the friction nanogenerator in Example 2 can convert light energy into heat energy and eliminate microorganisms, and has good photothermal antibacterial performance. The experimental results show that by combining the modified MXene with the gel material, the photothermal conversion efficiency of the composite hydrogel can be effectively improved, thereby improving the photothermal antibacterial property of the composite hydrogel, so that the friction nanogenerator containing the composite hydrogel can be applied to health care fields such as joint rehabilitation treatment and wound healing.
[0116] The above description has fully disclosed the specific implementation methods of the present application. It should be pointed out that any changes made by technicians familiar with the field to the specific implementation methods of the present application do not deviate from the scope of the claims of the present application. Accordingly, the scope of the claims of the present application is not limited to the above specific implementation methods.
Claims
1. A composite hydrogel, characterized in that: The composite hydrogel comprises a gel material and a modified MXene, wherein the modified MXene is obtained by surface-modifying the MXene with tannic acid and oxidized cellulose nanofibers.
2. The composite hydrogel according to claim 1, characterized in that The modified MXene satisfies at least one of the following characteristics: The mass ratio of the oxidized cellulose nanofibers, the tannic acid and the MXene in the modified MXene is 0.1-1.5:1:1; The chemical formula of the MXene is Ti3C2Tx, wherein Tx includes at least one of -O, -OH and -F.
3. The composite hydrogel according to claim 1, characterized in that The mass ratio of the gel material and the modified MXene in the composite hydrogel is 65:1-2.
4. The composite hydrogel according to claim 1, characterized in that The gel material includes at least one of polyacrylamide, polyhydroxyethyl methacrylate, polyacrylic acid and polyethylene glycol.
5. A method for preparing a composite hydrogel, characterized in that: include: S1: Provide MXene, tannic acid, oxidized cellulose nanofibers and gel monomers; S2: mixing the MXene and the tannic acid in a solvent to obtain a mixed solution; S3: adding the oxidized cellulose nanofibers into the mixed solution to obtain a modified MXene dispersion; S4: Mixing and cross-linking the modified MXene dispersion with the gel monomer to obtain a composite hydrogel.
6. The preparation method according to claim 5, characterized in that: The S1 includes: Providing lithium fluoride powder, titanium aluminum carbide powder and hydrochloric acid; dissolving the lithium fluoride powder in the hydrochloric acid to obtain a hydrofluoric acid solution; Adding the titanium aluminum carbide powder into the hydrofluoric acid solution for etching to obtain a MXene mixed solution; The MXene mixed liquid is washed and collected to obtain the MXene.
7. The preparation method according to claim 5, characterized in that: The S2 satisfies at least one of the following characteristics: The pH of the solvent is 8-9; The mixing time is 11-13 hours.
8. The preparation method according to claim 5, characterized in that: The S4 includes: Provide initiators, cross-linkers and catalysts; The modified MXene dispersion, the gel monomer, the initiator, the cross-linking agent and the catalyst are fully mixed and reacted to obtain the composite hydrogel.
9. The preparation method according to claim 8, characterized in that: The initiator includes at least one of ammonium persulfate and sodium persulfate, the crosslinking agent includes at least one of N,N-methylenebisacrylamide and ethylene glycol dimethacrylate, and the catalyst includes at least one of triethylenediamine and tetramethylethylenediamine.
10. A friction nanogenerator, characterized in that: The invention comprises the composite hydrogel as described in any one of claims 1 to 4.